Bone Marrow-Derived Cells Contribute to the Maintenance of Thymic Stroma including TECs - Shami Chakrabarti; Mohammed Hoque; Nawshin Zara Jamil; Varan J. Singh; Daniel Pollacksmith; Neelab Meer; Mark T. Pezzano (Journal of Immunology Research)
In paradox to critical functions for T-cell selection and self-tolerance, the thymus undergoes profound age-associated atrophy and loss of T-cell function, further enhanced by cancer therapies. Identifying thymic epithelial progenitor populations capable of forming functional thymic tissue will be critical in understanding thymic epithelial cell (TEC) ontogeny and designing strategies to reverse involution. We identified a new population of progenitor cells, present in both the thymus and bone marrow (BM) of mice, that coexpress the hematopoietic marker CD45 and the definitive thymic epithelial marker EpCAM and maintain the capacity to form functional thymic tissue. Confocal analysis and qRT-PCR of sorted cells from both BM and thymus confirmed coexpression of CD45 and EpCAM. Grafting of C57BL/6 fetal thymi under the kidney capsule of H2BGFP transgenic mice revealed that peripheral CD45+ EpCAM+ GFP-expressing cells migrate into the developing thymus and contribute to both TECs and FSP1-expressing thymic stroma. Sorted BM-derived CD45+ EpCAM+ cells contribute to reaggregate thymic organ cultures (RTOCs) and differentiate into keratin and FoxN1-expressing TECs, demonstrating that BM cells can contribute to the maintenance of TEC microenvironments previously thought to be derived solely from endoderm. BM-derived CD45+ EpCAM+ cells represent a new source of progenitor cells that contribute to thymic homeostasis. Future studies will characterize the contribution of BM-derived CD45+ EpCAM+ TEC progenitors to distinct functional TEC microenvironments in both the steady-state thymus and under conditions of demand. Cell therapies utilizing this population may help counteract thymic involution in cancer patients.